Enantioselective Synthesis of 4‑Aminotetrahydroquinolines via 1,2-Reductive Dearomatization of Quinolines and Copper(I) Hydride-Catalyzed Asymmetric Hydroamination - Xu-Xu, Qing-Feng; Zhang, Xiao; You, Shu-Li (Organic letters, 2019)
A 1,2-reductive dearomatization of quinolines and copper(II) acetate monohydrate/(R,R)-Ph-BPE/P(p-tolyl)3-catalyzed enantioselective hydroamination sequence was developed, affording diverse 4-amino-1,2,3,4-tetrahydroquinolines with high levels of enantioselectivity in either a stepwise or one-pot fashion. Pleasingly, internal cis-cyclic alkenes, which are challenging substrates in copper hydride-catalyzed enantioselective hydroamination reactions, were transformed efficiently under mild conditions.